Corona protein impacts on alternating current biosusceptometry signal and circulation times of differently coated MnFe2O4nanoparticles - Prospero, Andre Gonçalves [UNESP]; Buranello, Lais Pereira [UNESP]; Fernandes, Carlos Ah [UNESP]; Dos Santos, Lucilene Delazari [UNESP]; Soares, Guilherme [UNESP]; C Rossini, Bruno [UNESP]; Zufelato, Nícholas; Bakuzis, Andris Figueiroa; De Mattos Fontes, Marcos R [UNESP]; De Arruda Miranda, José R [UNESP] (Taylor & Francis, 2021)
Background: We evaluated the impacts of corona protein (CP) formation on the alternating current biosusceptometry (ACB) signal intensity and in vivo circulation times of three differently coated magnetic nanoparticles (MNP): bare, citrate-coated and bovine serum albumin-coated MNPs. Methods: We employed the ACB system, gel electrophoresis and mass spectrometry analysis. Results: Higher CP formation led to a greater reduction in the in vitro ACB signal intensity and circulation time. We found fewer proteins forming the CP for the bovine serum albumin-coated MNPs, which presented the highest circulation time in vivo among the MNPs studied. Conclusion: These data showed better biocompatibility, stability and magnetic signal uniformity in biological media for bovine serum albumin-coated MNPs than for citrate-coated MNPs and bare MNPs.
Keywords: alternating current biosusceptometry; biomedical engineering; corona protein; magnetic nanoparticles; mass spectrometry